2020
DOI: 10.1002/cctc.201901966
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of γ‐Valerolactone to Ethyl Valerate over Metal Promoted Ni/ZSM‐5 Catalysts: Influence of Ni0/Ni2+ Heterojunctions on Activity and Product Selectivity

Abstract: Promoter (Cr, Mo and W) modified Ni/ZSM‐5 catalysts were explored in the vapor phase conversion of γ‐valerolactone (GVL) to ethyl valerate (EV; gasoline blender) at atmospheric pressure. Among the three different promoters (Cr, Mo and W) tested the Mo‐modified catalyst was found to be the best candidate. In addition, this catalyst was found to be stable up to 50 h reaction time with an insignificant decrease in activity. The good catalytic performance is related to an optimal ratio of acid and hydrogenation fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The aqueous phase reforming (APR) process allows the mild and selective conversion of lignocellulose to versatile value-added chemicals and fuel molecules that has greatly enriched the downstream chemical family. , Several building blocks were selected by the US Department of Energy as platform molecules, which can be readily prepared from raw biomass and further converted to multifunctional chemicals through different technologies . Levulinic acid (LA) and its esters were included as platform molecules due to their ease of scale-up production via acid-hydrolysis/alcoholysis from carbohydrates and high reactivity to be transformed into a wide range of chemicals such as γ-valerolactone, 2-methyltetrahydrofuran (2-MTHF), 1,4-pentanediol (1,4-PeD), , and valerate acid/ester. Particularly, 2-methyltetrahydrofuran (2-MTHF) has drawn much attention as a fuel molecule, possessing good hydrophobicity, high heating value, and a suitable octane number, indicating that it can be directly blended up to 70% of regular gasoline …”
Section: Introductionmentioning
confidence: 99%
“…The aqueous phase reforming (APR) process allows the mild and selective conversion of lignocellulose to versatile value-added chemicals and fuel molecules that has greatly enriched the downstream chemical family. , Several building blocks were selected by the US Department of Energy as platform molecules, which can be readily prepared from raw biomass and further converted to multifunctional chemicals through different technologies . Levulinic acid (LA) and its esters were included as platform molecules due to their ease of scale-up production via acid-hydrolysis/alcoholysis from carbohydrates and high reactivity to be transformed into a wide range of chemicals such as γ-valerolactone, 2-methyltetrahydrofuran (2-MTHF), 1,4-pentanediol (1,4-PeD), , and valerate acid/ester. Particularly, 2-methyltetrahydrofuran (2-MTHF) has drawn much attention as a fuel molecule, possessing good hydrophobicity, high heating value, and a suitable octane number, indicating that it can be directly blended up to 70% of regular gasoline …”
Section: Introductionmentioning
confidence: 99%
“…Most of the reported systems are based on a liquid phase reaction at high pressure; the continuous- flow mode has been of less concern. Velisoju et al 83 investigated the ring-opening hydrogenation of GVL to ethyl valerate over Cr, Mo, W promoted Ni/ZSM-5 in the vapor phase under ambient pressure conditions. They found that doping of the metal Mo significantly enhanced the selectivity of ethyl valerate (EtVal) due to the formation of the mixed metal oxide phase NiMoO 4 , providing lower Ni(0) species and BAS/LAS ratio, which was demonstrated to favor EtVal production.…”
Section: Converting Leva and Gvl Into Alkyl Valeratesmentioning
confidence: 99%
“…These weak LAS acid centers are capable of opening the ring of GVL, their less intrinsic activity is compensated with the higher concentration of these centers. Recently Velisoju et al 45 have described the formation of Ni 2+ /Ni 0 in Ni/ZSM5 catalysts promoted by the incorporation of Mo. They suggest that the Ni 2+ species stabilized by interaction with Mo can perform the GVL opening ring by cracking the C-O bond on the methyl group side of the GVL molecule.…”
Section: Role Of the Surface Acidity On The Catalytic Propertiesmentioning
confidence: 99%